ANALYSIS OF USER EXPERIENCE TESTING STMIK AKI WEBSITE USING SUPR-Q IN PERSPECTIVE HUMAN-COMPUTER INTERACTION - Eko Prasetyo; Kristiawan Nugroho; Kristophorus Hadiono (LPPM Politeknik Saint Paul Sorong, 2023)
Human-Computer Interaction (HCI) is a scientific field that studies human-computer interaction in order to design systems that satisfy user requirements and enhance the user experience (UX). HCI is very important in the development of websites because a good user experience is necessary to improve user satisfaction, efficiency, and effectiveness. The motivation behind this study is to recognize the qualities and shortcomings of the STMIK AKI site as far as client experience, as the need might have arisen to further develop client UX. From a HCI perspective, SUPR-Q is one way to use a questionnaire to measure user experience. To analyze various UX dimensions, UX testing will use Task Level Satisfaction methods like Single Ease Question (SEQ), Scenario Testing, and System Usability Scale (SUS) in addition to the SUPR-Q method. The SUPR-Q Loyalty variable had a low value, but the SEQ, SUS, and SUPR-Q methods produced results with an average grade of B, supporting the hypothesis that respondents were satisfied with their use of the STMIK AKI website. The worth got was 59.1% with Grade C and the speculation was adequate in utilizing and suggesting the STMIK AKI site page. Furthermore, in the Situation Testing strategy, the typical worth got is 57.5% with Grade C, with the speculation that the respondent or client is very able in finishing jobs or working the STMIK AKI page framework.